Logical Semantic and Figurative Modeling of Phraseological Units in Arabic: Логико-Семиотическое И Образное Моделирование Фразеологизмов В Арабском Языке (Journal of the College of Languages (JCL), 2021)
The present article is devoted to the analysis of Arabic phraseological units with a component hand, selected by continuous sampling from the “Training Russian-Arabic phraseological dictionary: about 900 phraseological units” by G. L. Permyakov. Arabic phraseological units with a component hand are modeled as invariant situations (by logical-semiotic models) and figurative statements are expressed by phraseological variants (according to the figurative characteristic of the hand component). The artical focuses on the fact that somatism in Arabic phraseology has a symbolic and symbolic nature, marking various situations of Arabs' behavior, their actions, deeds, rituals, emotional and psychological states, etiquette, in particular etiquette formulas of congratulations and politeness. Thus, Arabic phraseology encodes these situations as invariants, for which phraseological variants are used with the component hand, which is the figurative and symbolic center of formation of their intended phraseological meaning. АннотацияСтатья посвящена анализу арабских фразеологизмов з компонентом рука, отобранные путем сплошной выборки из «Учебного русско-арабского фразеологического словаря: около 900 фразеологизмов» Г. Л. Пермякова арабские фразеологизмы с компонентом рука смоделированы в качестве инвариантных ситуаций (по логико-семиотическим моделям) и как образные высказывания, выраженные фразеологическими вариантами (по образной характеристике компонента рука). Автор акцентирует внимание на том, что соматизм рука в арабской фразеологии имеет знаково-символическую природу, маркируя различные ситуации поведения арабов, их действия, поступки, обряды, эмоциональные и психологические состояния, этикет, в частности этикетные формулы поздравления и вежливости. Таким образом, арабская фразеология кодирует эти ситуации как инварианты, для обозначения которых используются фразеологические варианты с компонентом рука, который является образно-символическим центром образования их фразеологического значения.